Tingkat Bagi Hasil, Pertumbuhan Likuiditas, dan Produk Domestik Bruto Terhadap Simpanan Mudharabah - Ismayana Marhamah (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2017)
This study aims to determine the effect of profit sharing growth, liquidity growth, gross domestic product (GDP) growth, of mudharabah saving growth in general islamic banks. The variables studied are the influence of profit sharing rate, liquidity growth, gross domestic product (GDP) growth as independent variable and mudharabah saving growth as dependent variable. The population in this study are sharia islamic banks registered in Bank Indonesia (BI) and the amount of gross domestic productquarter-year period 2012-2016.The result of hypothesis testing (t test) shows that the profit sharing growth and gross domestic product partially has significant effect to mudharabah saving growth. Then the test result of liquidity growth partially has no effect and not significant to mudharabah saving growth. The results of simultaneous hypothesis test (test F), show that all independent variabels in this study has significant effect to mudharabah saving growth.